Correction: A novel NDUFS3 mutation in a Chinese patient with severe Leigh syndrome. Issue 12 (December 2018) - Lou, Xiaoting; Shi, Hao; Wen, Shumeng; Li, Yuanyuan; Wei, Xiujuan; Xie, Jie; Ma, Lin; Yang, Yanling; Fang, Hezhi; Lyu, Jianxin
The originally published version of this article contained an error in Figure 1. The correct figure of this article should have read as below. This has now been corrected in the PDF and HTML versions of the article. The authors apologize for any inconvenience caused.